[Two Society of Black Business Students (SBBS) members inside Open House tent] (1995)
The two students are smiling, and one of them is playfully gesturing towards the camera. One student has an apron that reads 'Coffee Society'. There is a snow cone machine, snow cone syrup, bottles of water, candy, and sodas in the tent behind the students.